Gambaran tingkat kecemasan pada ibu hamil primigravida dalam menghadapi persalinan - Nurhayati Nurhayati; Marliyana Marliyana; Dwi Nuraini (JOURNAL OF Mental Health Concerns, 2023)
Background: Anxiety during pregnancy is often found in primigravid pregnant women, especially in the third trimester. Anxiety is an unpleasant emotion characterized by worry, concern and fear that arises naturally and at different levels. Purpose: To obtain an overview of the anxiety level of third trimester primigravid pregnant women at the Barokah Medika Kemiling Clinic in Bandar Lampung in 2023. Method: The type of research used is descriptive, with a quota sampling technique where researchers use the Hamilton anxiety rating scale questionnaire to measure anxiety levels. Respondents to scientific papers were primigravida third trimester pregnant women who visited the Barokah Medika Kemiling Clinic in Bandar Lampung in May 2023, totaling 30 respondents. Results: The level of anxiety in 30 respondents was found to be 3 (10%) respondents with severe anxiety levels, 5 (16.7%) respondents with moderate anxiety, 9 (30%) respondents with mild anxiety, and 13 (43.3%) with no anxiety. %) respondents. Conclusion: Pregnant women with no anxiety have the highest percentage. Suggestion: It is hoped that primigravida pregnant women will carry out Ante Natal Care (ANC) regularly at least 4 times during pregnancy, this can provide information regarding the mother's pregnancy, so that the health of the mother and baby can be well controlled. It is hoped that future researchers can continue this research, for example with the effect of pregnancy exercise on third trimester primigravida pregnant women in dealing with anxiety, so that the research results are expected to be more varied. Keywords: Anxiety, Childbirth, Primigravida Pregnant Women. Pendahuluan: Kecemasan selama kehamilan sering ditemukan pada ibu hamil primigravida, terutama pada trimester ketiga. Cemas merupakan emosi tidak menyenangkan yang ditandai dengan kekhawatiran, keprihatinan dan rasa takut yang timbul secara alami dan dalam tingkat yang berbeda. Tujuan: Untuk medapatkan gambaran tingkat kecemasan ibu hamil primigravida trimester III di Klinik Barokah Medika Kemiling Bandar Lampung tahun 2023. Metode: Jenis penelitian yang digunakan adalah deskriptif, dengan teknik pengambilan sampel quota sampling dimana peneliti menggunakan kuesioner Hamilton anxiety rating scale untuk mengukur tingkat kecemasan. Responden karya tulis ilmiah ialah ibu hamil primigravida trimester III yang berkunjung ke Klinik Barokah Medika Kemiling Bandar Lampung pada bulan Mei 2023 sebanyak 30 responden. Hasil: Tingkat kecemasan pada 30 responden didapatkan responden dengan tingkat kecemasan berat 3 (10%) responden, kecemasan sedang sebanyak 5 (16,7%) responden, kecemasan ringan 9 (30%) responden, dan tidak ada kecemasan 13 (43,3%) responden. Simpulan: Ibu hamil dengan tidak ada kecemasan memiliki persentase tertinggi. Saran: Diharapkan kepada ibu hamil primigravida melakukan Ante Natal Care (ANC) secara rutin sedikitnya 4 kali selama kehamilan, hal tersebut dapat memberikan informasi terkait kehamilan ibu, sehingga kesehatan ibu dan bayi dapat terkontrol dengan baik. Bagi peneliti selanjutnya diharapkan dapat melanjutkan penelitian ini misalnya dengan pengaruh senam hamil terhadap ibu hamil primigravida trimester III dalam menghadapi kecemasan, sehingga hasil penelitian diharapkan lebih bervariasi.